POTVIN DOUBLE-COUNT AERIAL SURVEYS IN NEW BRUNSWICK: ARE RESULTS RELIABLE FOR MOOSE? - Cumberland, Roderick E (Lakehead University, 2012)
Following the rapid decline of deer (Odocoileus virginianus) across northern New Brunswick in the late 1980s, the New Brunswick Department of Natural Resources began to utilize a double-count helicopter survey to estimate deer numbers. Although the survey was designed for deer, moose (Alces alces) sightings were also recorded; however, no analysis was conducted on the accuracy or usefulness of these data to estimate moose numbers. The survey design was a modification of the Potvin double-count survey method for deer which accounts for most caveats to aerial surveys. This double-count (mark-recapture) technique allows calculation of bias for both observers, for single and groups of moose, and individual flights. Moose population estimates calculated from 79 flights ranged from 0.17-3.49 moose/km2 and were similar to a variety of estimates throughout North America. Population estimates from 2004-2009 correlated well with corresponding 2009 population indices for moose based on number of moose seen by deer hunters (Corr. = 0.725, P <0.001). The Potvin estimates in Wildlife Management Zone 2 were highly correlated (0.82-0.93, P <0.05) with other indices based on road kill moose, moose sightings, and harvest success rates; moose sightings and hunter success were also correlated in several other zones. This analysis indicates that Potvin surveys produce reliable population density estimates of moose in boreal/Acadian forests, given that the sighting probability is >0.4 and flights occur before mid-February when moose may occupy denser canopy cover.